2021
DOI: 10.1007/s41042-021-00051-1
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining High Eudaimonic Wellbeing Despite Ambiguity Intolerance Among Three Employment Status Groups: Examining the Buffering Effects of Positive Psychological Attributes

Abstract: The unemployed, as well as individuals in self and salaried employment, face several work-related risks and uncertainties which can result in diminished psychological wellbeing especially for individuals with high ambiguity intolerance. However, positive psychology literature suggests that individuals with strong psychological resources can be resilient in difficult circumstances. Using a sample of 922 individuals (including 240 unemployed, 391 salary-employed, and 291 self-employed) from Uganda and Kenya, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 126 publications
(213 reference statements)
1
9
0
Order By: Relevance
“…Moreover, past research has provided robust evidence for the association between IU and the different components of well-being (Baluku et al, 2022; Bardeen et al, 2013; Rasmussen et al, 2013; Shoychet et al, 2022). For instance, Morse et al (2021) indicated that people who are tolerant of uncertainty find more meaning in their lives, while people who experience increased IU often function at a lower level of meaning formation to calm their anxiety and seek solace in certainties.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, past research has provided robust evidence for the association between IU and the different components of well-being (Baluku et al, 2022; Bardeen et al, 2013; Rasmussen et al, 2013; Shoychet et al, 2022). For instance, Morse et al (2021) indicated that people who are tolerant of uncertainty find more meaning in their lives, while people who experience increased IU often function at a lower level of meaning formation to calm their anxiety and seek solace in certainties.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…On the other hand, a study conducted by Reizer et al (2021) found that IU is a significant predictor of psychological distress, and an inability to cope with increased uncertainty can lead to increased levels of distress and lower levels of well-being. Moreover, past research has provided robust evidence for the association between IU and the different components of well-being (Baluku et al, 2022;Bardeen et al, 2013;Rasmussen et al, 2013;Shoychet et al, 2022). For instance, Morse et al (2021) indicated that people who are tolerant of uncertainty find more meaning in their lives, while people who experience increased IU often function at a lower level of meaning formation to calm their anxiety and seek solace in certainties.…”
Section: Students' Well-being In Times Of Uncertaintymentioning
confidence: 99%
“…While Rotter (1966) is certain to note that neither loci of control is inherently superior to the other, several studies indicate that a general orientation toward an internal locus of control is more frequently associated with benefits in a variety of areas, such as physical health, interpersonal relationships, academic achievement, and job performance (Hopkins et al, 2020;Levy & Gumpel, 2020;Kesavayuth et al, 2020;Strong & Gore, 2020). Given the evident benefits of orientation toward an internal locus of control, researchers have worked extensively to confirm the association between locus of control and various measures of psychological well-being (Baluku et al, 2021;Di Pentima et al, 2019;Enwere & Mbakwe, 2021;Skomorovsky & Wan, 2019). With a public interest in mental health awareness and an emphasis on positive psychology today, psychological well-being is a continuously growing area of research.…”
Section: Locus Of Controlmentioning
confidence: 99%
“…Several studies exploring the relationship between locus of control and psychological well-being indicate that an individual's locus of control may influence or predict their level of psychological well-being (Baluku et al, 2021;Di Pentima et al, 2019;Enwere & Mbakwe, 2021;Skomorovsky & Wan, 2019;Sona et al, 2020). Specifically, the findings of these studies suggest that a general orientation toward an internal locus of control is associated with higher levels of psychological well-being.…”
Section: Relationship Between Psychological Well-being and Locus Of Controlmentioning
confidence: 99%
See 1 more Smart Citation